Peningkatan Nilai Perusahaan Berbasis Profitabilitas dan Modal Kerja dengan Struktur Modal Sebagai Variabel Mediasi - Widyakto, Adhi; Riyanto, Sugeng; Fresiliasari, Oktavie; Rohman, Nur (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to test the effect of Return On Equity and Current Ratio on Company Value with capital structure as an intervening variable in coal mining companies listed on the Indonesia Stock Exchange for the period 2019-2023. This study was conducted by purposive sampling with certain criteria, so 36 coal mining companies were used as a research method. The sample used was 5 periods, so the final sample in this study was 180 observations. Data analysis was used using the SmartPLS application tool. The results of this study prove that Return On Equity has a significant positive effect on the equity Ratio, Current Ratio has a significant positive effect on the equity Ratio, Return On Equity has a positive and significant effect on Price Book Value, Current Ratio has a positive and insignificant effect on Price to Book Value, Debt Equity Ratio has a significant positive effect on Price Book Value, and the Return On Equity variable has a significant positive effect on Price to Book Value with Debt Equity Ratio as an intervening variable and Current Ratio has a significant positive effect on Price to Book Value with Debt Equity Ratio as an intervening variable